PENINGKATAN PENGETAHUAN WARGA KECAMATAN MANONJAYA TENTANG TANAMAN OBAT YANG DAPAT DIMANFAATKAN SEBAGAI ANTI INFLAMASI - Sutiswa, Shandra Isasi; Aji, Nur; Handayani, Nuri (Poltekkes Kemenkes Tasikmalaya, 2024)
Inflammation is the body's defense reaction against various kinds of stimuli. The visible signs of inflammation are redness, heat, swelling, pain, and loss of function. Anti-inflammatory drugs are generally the NSIAD group which causes side effects of stomach ulcers, nausea and vomiting. Currently, people tend to choose traditional medicine using medicinal plants that are rich in benefits. There are several medicinal plants that can be used as anti-inflammatories that are not widely known by the public. Manonjaya District has plantation land and yards that can be used to grow medicinal plants. Manonjaya District has a large millennial population who do a lot of physical activity which can trigger inflammation. The Tasikmalaya Ministry of Health Polytechnic, which is part of the City of Tasikmalaya, through its role in the Tri Dharma of Higher Education, especially in the community service program, aims to improve the health status of the community. The methods used in this activity were counseling about medicinal plants that can be used as anti-inflammatory agents and distributing pocket books on anti-inflammatory medicinal plants to 20 youth organizations. Evaluation of the results of activities to increase knowledge is carried out through pre-tests and post-tests. The pre-test and post-test scores were analyzed statistically using t-Test data analysis: Paired Two Samples for Means with a significance value of 0.05. The evaluation results show that the significance value is <0.05, meaning there is an increase in participants' knowledge about medicinal plants which can be used as anti-inflammatory agents.